A Randomized Controlled Trial of Enhanced Recovery After Surgery Versus Standard of Care Recovery for Emergency Cesarean Deliveries at Mbarara Hospital, Uganda - Moris, Baluku; Francis, Bajunirwe; Joseph, Ngonzi; Joseph, Kiwanuka; Stephen, Ttendo (International Anesthesia Research Society, 2020)
BACKGROUND: Enhanced recovery after surgery (ERAS) expedites return to patient baseline and functional status by reducing surgical trauma, stress, and organ dysfunction. Despite the potential benefits of enhanced recovery protocols, limited research has been done in lowresource settings, where 95% of cesarean deliveries are emergent and could possibly benefit from the application of ERAS protocols. METHODS: In a prospective, randomized, single-blind, controlled trial, mothers delivering by emergency cesarean delivery were randomly assigned to either an ERAS or a standard of care (SOC) recovery arm. Patients in the ERAS arm were treated with a modified ERAS protocol that included modified counseling and education, prophylactic antibiotics, antiemetics, normothermia, restrictive fluid administration, and multimodal analgesia. They also received early initiation of mobilization, feeding, and urethral catheter removal. The primary end point was length of hospital stay. The secondary end points were complications and readmission rates. Mean length of stay in the intervention and control arms were compared using t tests. Statistical analyses were performed using STATA version 13 (College Station, TX). RESULTS: A total of 160 patients were enrolled in the study, with 80 randomized to each arm. There was a statistically significant shorter length of stay for the ERAS arm compared to SOC, with a difference of −18.5 hours (P < .001, 95% confidence interval [CI], −23.67, −13.34). The incidence of complications of severe pain and headache was lower in the ERAS arm compared to SOC (P = .001 for both complications). However, pruritus was more common in the ERAS arm compared to SOC (P = .023). CONCLUSIONS: Use of an ERAS protocol for women undergoing emergency cesarean delivery in a low-income setting is feasible and reduces length of hospital stay without generally increasing the complication rate. (Anesth Analg 2020;130:769–76)